2014
DOI: 10.1638/2012-0250.1
|View full text |Cite
|
Sign up to set email alerts
|

PREVALENCE OFSALMONELLASPP. AND THERMOPHILICCAMPYLOBACTERSPP. IN THE SMALL ASIAN MONGOOSE (HERPESTES JAVANICUS) IN BARBADOS, WEST INDIES

Abstract: From April to July 2005, rectal swabs were collected from 48 free-ranging small Asian mongooses (Herpestes javanicus) on the east and south coasts of Barbados and analyzed for Salmonella and Campylobacter spp. Salmonella was recovered in 21.12% (7/33) of mongooses at the east-coast site and 26.67% (4/15) at the south-coast site. Four serotypes were isolated: Salmonella enterica serovar Rubislaw, Kentucky, Javiana, and Panama. One east-coast sample of 11 tested for Campylobacter was positive (9.09%). These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Campylobacter spp. has previously has been found in the small Indian mongoose (Herpestes auropunctatus), a predominantly solitary species, but at significantly lower levels (2.4-9%) [56,57] then that found in banded mongooses (56%, 95% CI 46-65%). A number of banded mongoose behaviors may contribute to observed elevations in infection.…”
Section: Campylobacter Spp Presence In Banded Mongoosesmentioning
confidence: 88%
“…Campylobacter spp. has previously has been found in the small Indian mongoose (Herpestes auropunctatus), a predominantly solitary species, but at significantly lower levels (2.4-9%) [56,57] then that found in banded mongooses (56%, 95% CI 46-65%). A number of banded mongoose behaviors may contribute to observed elevations in infection.…”
Section: Campylobacter Spp Presence In Banded Mongoosesmentioning
confidence: 88%
“…and Campylobacter spp. have been reported in free-ranging mongooses on Barbados (Rhynd et al 2014;Matthias and Levett 2002), and although rabies is not present in Hawaii, the mongoose is the primary rabies reservoir on Puerto Rico, Cuba, Grenada, the Dominican Republic, and most likely Haiti (Everard and Everard 1992;Zieger et al 2014;Berentsen et al 2015).…”
Section: Diseasementioning
confidence: 98%
“…Data from the articles reviewed showed that at least twelve Campylobacter species have been detected in wild animals in 36 countries and the Antarctica Peninsula [ 15 , 16 , 38 , 40 , 41 , 42 , 43 , 46 , 48 , 49 , 50 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ...…”
Section: Wildlife Carriers Of Campylobacter Speciesmentioning
confidence: 99%
“…On the other hand, a cross-sectional study of the molecular epidemiology of C. jejuni in a dairy farmland environment [ 46 ] showed that 73.7% of wild rabbits ( Oryctolagus cuniculus ) can keep a similar genotype in cattle (the ST-21 complex), which is relevant to human infection. Rhynd et al [ 85 ] demonstrated that asian mongooses ( Herpestes javanicus ) are carriers and shedders of Salmonella and Campylobacter spp. Moreover, Medley et al [ 66 ] sampled fecal samples in humans, free-ranging banded mongooses ( Mungos mungo ) surface water, and river sediment samples in northern Botswana and reported Campylobacter spp.…”
Section: Wildlife Carriers Of Campylobacter Speciesmentioning
confidence: 99%